Acute Headache in the Emergency Department: Is Lumbar Puncture Still Necessary to Rule Out Subarachnoid Hemorrhage?. (April 2018) - Steffens, Sarah; Tucker, Paula; Evans, Dian Dowling
Abstract : The purpose of the Research to Practice column is to review current primary journal articles that directly affect the practice of the advanced practice nurse (APN) in the emergency department. This review examines the findings of Carpenter et al. (2016) from their article, "Spontaneous Subarachnoid Hemorrhage: A Systematic Review and Meta-Analysis Describing the Diagnostic Accuracy of History, Physical Exam, Imaging, and Lumbar Puncture With an Exploration of Test Thresholds." The authors concluded that although no history or physical examination finding can be used to rule in or rule out spontaneous subarachnoid hemorrhage (SAH), the complaint of neck stiffness can increase the likelihood of SAH. In addition, the authors concluded that noncontrast head computed tomography (CT) is accurate in ruling out/in SAH when performed within 6 hr of symptom onset in adults with symptoms consistent with SAH and that the traditional gold standard of confirmatory lumbar puncture after a negative head CT scan is only helpful in patients with a very high pretest probability of SAH. By applying the evidence-based criteria presented in this study, the emergency department APN can confidently rule out SAH and reduce patient risks from unnecessary invasive and costly testing.